Evaluation of E-Government Using COBIT 5 Framework (Case Study of Sistem Database Pemasyarakatan Implementation in Ministry of Law and Human Rights in the Special Region of Yogyakarta) - Fanny Novianto; Maria Ulfah Siregar (IJID (International Journal on Informatics for Development), 2019)
Information technology has become an important element in the industrial era 4.0, an era where the concept of automation is known in the production process carried out by technology by reducing the role of humans in its application. Since the issuance of Presidential Instruction Number 3/2003 concerning National Policies and Strategies for E-Government Development, both central government and local governments, have begun to move to develop e-government in their respective regions. The Ministry of Law and Human Rights of the Republic of Indonesia is currently implementing e-government in internal business processes and public services that aimed at serving prime communities, eliminating illegal payments, and creating transparent and accountable performance. One of them is the use of the Sistem Database Pemasyarakatan (SDP). Data and information in the SDP are confidential because one of them contains data and information on criminals in Indonesia. The research method used is a quantitative method using a questionnaire instrument and using the 5th edition of the COBIT framework model and emphasizes on information security. From the gap analysis, it can be recommended one of them is Organizations must integrate security into every facet of management and operations. This begins with identifying all business processes and associated stakeholders, including audit.